Analysing Cost-Effectiveness Of Raising Learning For Marginalised Girls Through Camfed'S Programme: Methodological A Methodological Note - Delprato, Marcos; Alcott, Benjamin; Rose, Pauline; Sabates, Ricardo (Zenodo, 2017)
This note provides an overview of the methodological approach being taken to analyse cost-effectiveness of Camfed’s programme in Tanzania and Zimbabwei. It highlights the association between Value for Money and cost-effectiveness, and pays particular attention to the importance of measuring cost-effectiveness from an equity perspective. It further identifies the implications of calculating cost-effectiveness with consideration of sustainability, scalability and replicability of Camfed’s programme.